Ressignificações identitárias : O caso dos B'nei Anussim em Recife (1970-2000) - BRITO, Creso Nuno Moraes de (2014)
The present research pursuits understand the formation of the group so called anussim or Marranos and the dispute over Jewish identity legitimation with other Jewish groups in the city of Recife, in Brazil. Claiming to be the descendants of the old settler and of iberic newchristians (who were originally sefardim) that came to Brazil in colonial times, the anussim attempt to be officially recognized as members of the jewish community by the present participants of the israelit community, wich is composed in its majority by askhenazis (the center and east-european jews). Organized individually or in groups since the early seventies, the marranos want to be recognized as part of the jewish comunity, thus through the traditional way of conversion (guiur) or by the controversial return (teshuvah). By affirming the urge of recognition as jews for descending of jewish, even if those have been converted to cristhianism, and maintaining certain habits so called judaizantes (of jewish origin), they question the formalities strict rules of insertion in judaism, wich demands a maternal descendency or a religious conversion. Formimg a very heterogeneous group when it comes to interpretation and religious practices, despite affirming an official commom speech, they are also diverse in concern of belonging to different social statements. However, because they consider themselves heirs of the 17th century jewish-portuguese community, it is possible to argue with the usual historiography, which is quite silent about the fate of those jews and newchristians after the deutsch surrender. A goal of creating an link between the jewish communities of today and yore.